Reinforcement Of Natural Rubber And Epoxidized Natural Rubbers With Amine-Treated Silica - Surya, Indra (2002)

(untitled)
Pengkajian mengenai kesesuaian penggunaan silika terawat amina untuk pengukuhan getah-getah SMR-L, ENR 25 dan ENR 50 telah dilakukan. Silika terawat amina disediakan melalui proses perawatan amina, dimana silika normal dirawat didalam larutan butilamina dengan pH yang tertentu. The feasibility study of utilising amine-treated silica on reinforcement of SMR-L, ENR 25 and ENR 50 by using semi-efficient (semi-EV) system was carried out. The amine-treated silica was prepared by treating normal silica filler in a butylamine solution with a certain pH.